ANALISIS YURIDIS PENJATUHAN HUKUMAN KEPADA PELAKU TINDAK PIDANAKEKERASAN SEKSUAL KEPADA ANAK (Studi Kasus Putusan Nomor 1268/K/Pid.Sus/2019). - Candra Purnama Laia (Jurnal Panah Hukum, 2022)
Children are creations of God Almighty, who since in the womb already have the right to life and independence and receive good protection from parents, family, community, nation and state. Given the importance of the role of children, children's rights have been explicitly regulated in Article 28 B paragraph (2) of the 1945 Constitution, stating that every child has the right to survive, grow and develop and has the right to protection from violence and discrimination. Crime is a reality in social life that deserves special attention. The formulation of the problem in this study is how the judges consider in imposing a sentence on perpetrators of sexual violence against children (case study of Decision Number 1268/K/Pid.Sus/2019)? The purpose of this study is to find out and analyze the judge's considerations in imposing a sentence on perpetrators of sexual violence against children (case study Decision Number 1268/K/Pid.Sus/2019). This type of research is a normative legal research using a statutory approach, a case approach, and an analytical approach. Data collection is done by using secondary data obtained through literature study consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is qualitative analysis. Based on the results of research and discussion that the judge's considerations in imposing a sentence on perpetrators of sexual violence against children (case study Decision Number 1268/K/Pid.Sus/2019), it was concluded that the defendant's actions were proven to have violated the provisions as stipulated in Article 81 paragraph (1) junto Article 76d of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection as stated in Decision Number 1268/K/Pid.Sus/2019. Based on the author's analysis of the elements in Article 76d, that is, everyone is prohibited from committing violence or threats of violence, forcing a child to have intercourse with him or with other people. Meanwhile, the history of the defendant's actions from the introduction of the victim to committing non-violent sexual intercourse.